Child Nutrition Problems and Measures of the Struggle During the Great Patriotic War (1941–1945) (to the 80 Years of Victory in the Great Patriotic War) - Stella A. Sher; Valery Yu. Albitskiy (Педиатрическая фармакология)
The article presents the results of a historical and medical study reflecting the problems of child food during the Great Patriotic War of 1941–1945. The purpose of the study is to conduct an objective analysis of the situation related to the shortage of child food in the most difficult period of the history of our country and give an impartial assessment of the state measures taken to solve the problems that have arisen. An analysis of archival and literary sources indicates that providing children with food during the war was one of the most difficult tasks of high-priority importance. Deprived of vital nutrients and vitamins that guarantee normal growth and development processes, children of war suffered from hypotrophy, hypovitaminosis, rickets, they had а physical and psychomotor retardation, a decrease of the body resistance. Despite the extraordinary circumstances, a set of state measures was implemented to ensure the need of the child’s body for the necessary vital nutrients and vitamins. However, some territories had difficulties of an objective and organizational nature with the supply of food to children. To save the lives of young children, their normal physical and psychomotor development, reduce morbidity and mortality, scientists conducted research in order to obtain alternative food sources rich in proteins, fats, carbohydrates and vitamins that replace children’s foods that were scarce during the war.